2021
DOI: 10.2174/1568026621666210331161144
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Metabolic Reaction Networks with Perturbation-Theory Machine Learning (PTML) Models

Abstract: Background: Checking the connectivity (structure) of complex Metabolic Reaction Networks (MRNs) models proposed for new microorganisms with promising properties is an important goal for chemical biology. Objective: In principle, we can perform a hand-on checking (Manual Curation). However, this is a hard task due to the high number of combinations of pairs of nodes (possible metabolic reactions). Method: In this work, we used Combinatorial, Perturbation Theory, and Machine Learning, techniques to seek a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This means that the LQI descriptor for a molecule will have the same value regardless of the experimental condition cj used to assess the anti-TB activity of that molecule. To solve this inconvenience, we applied the adaptation of the Box–Jenkins approach, which is a distinctive characteristic of all the PTML models [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 55 ]: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the LQI descriptor for a molecule will have the same value regardless of the experimental condition cj used to assess the anti-TB activity of that molecule. To solve this inconvenience, we applied the adaptation of the Box–Jenkins approach, which is a distinctive characteristic of all the PTML models [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 55 ]: …”
Section: Methodsmentioning
confidence: 99%
“…To solve the aforementioned limitations, several researchers have emphasized the use of interpretable in silico models focused on a combination of perturbation theory concepts and machine learning techniques (PTML) [ 15 , 16 , 17 ], which can integrate different sources of chemical and biological data, enabling the simultaneous prediction of multiple biological endpoints against many targets of varying degrees of complexity. Seminal works on PTML models have found successful applications in diverse research areas such as infectious diseases [ 18 , 19 ], oncology [ 20 , 21 ], neuroscience [ 22 , 23 , 24 , 25 ], proteomics [ 26 ], metabolomics [ 27 ], nanotechnology [ 28 , 29 , 30 , 31 ], toxicology [ 32 ], and immunology and immunotoxicity [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Novel applications of MN reconstructions of human pathogens have recently been described. These studies have focused on elucidating resistance metabolic dependencies and identifying potential drug targets and antibiotics. The influence of the changes in MNs on the capacity of various microorganisms to survive has been demonstrated by Barabási′s team and other authors. , …”
Section: Introductionmentioning
confidence: 99%
“…28 In addition, Duardo-Sanchez et al, Riera-Fernández et al, and others reported IFPTML models of MN but not included AD or NP components. [29][30][31][32] Consequently, IFPTML has been used before to solve parts of the present problem. However, there are no reports of IFPTML models including the three components AD, NP, and MN of this problem at the same time.…”
Section: Introductionmentioning
confidence: 99%